Sosialisasi Penguatan Proyek Profil Pelajar Pancasila (P5) Melalui Kewirausahaan Berbasis Kearifan Lokal di SMA Negeri 2 Seram Bagian Barat (SBB) - Manuhutu, Silvia (Universitas Pattimura, 2023)
One of the key features of the implementation of the Kurikulum Merdeka Belajar is the Pancasila Student Profile Project (P5), which includes various themes aimed at developing students' competencies and character. One of the themes addressed is entrepreneurship, which trains and educates students to become creative, critical thinkers, independent, resilient, and innovative. The goal of this community service (PKM) activity is to provide understanding and strengthen both teachers and students on the importance of cultivating entrepreneurial character through various entrepreneurship projects, so that when students enter society, they are not only job seekers but can also create job opportunities for themselves. The activity methodology is directed towards delivering material and group discussions to generate local wisdom-based entrepreneurial ideas, particularly those based on local food resources found in the students' communities. Success indicators are measured based on student participation and their positive response to actively engage in the PKM activities, as well as the entrepreneurial ideas generated through group work activities. The resulting ideas reflect several entrepreneurial characteristics, including having numerous ideas, sensitivity to the environment and opportunities, creativity, independence, discipline, honesty, willingness to take risks, and a future-oriented mindset.